2007
DOI: 10.1186/1749-8090-2-46
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery surgery: cardiotomy suction or cell salvage?

Abstract: Coronary artery bypass grafting (CABG) today results in what may be regarded as acceptable levels of blood loss with many institutions avoiding allogeneic red cell transfusion in over 60% of their patients. The majority of cardiac surgeons employ cardiotomy suction to preserve autologous blood during on-pump coronary artery bypass surgery; however the use of cardiotomy suction is associated with a more pronounced systemic inflammatory response and a resulting coagulopathy as well as exacerbating the microembo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Conversely, the cardiotomy suction component of a CPB system is the major source of hemolysis because of the amount of air that is aspirated together with the blood [79]. Beside the intensity of mechanical shear stress, RBCs can also have different susceptibilities to this stress, such as pediatric RBCs or RBCs exposed to hypothermia or hemodilution solutions which do not have plasma proteins.…”
Section: Optimizing Cardiac Surgical Procedures and Cpb Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, the cardiotomy suction component of a CPB system is the major source of hemolysis because of the amount of air that is aspirated together with the blood [79]. Beside the intensity of mechanical shear stress, RBCs can also have different susceptibilities to this stress, such as pediatric RBCs or RBCs exposed to hypothermia or hemodilution solutions which do not have plasma proteins.…”
Section: Optimizing Cardiac Surgical Procedures and Cpb Parametersmentioning
confidence: 99%
“…During blood processing, only RBCs are retained while the plasma, platelets, heparin, plasma-free hemoglobin (PfHb), and inflammatory mediators are discarded with the wash solution. The resulting RBCs are finally suspended at a hematocrit of 50-70% in normal saline and reinfused [79]. As of now, there are no data regarding the impact of such blood-sparing techniques on renal outcomes.…”
Section: Optimizing Cardiac Surgical Procedures and Cpb Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well-demonstrated that the use of plain cardiotomy suction without ultrafiltration is associated with a more pronounced systemic inflammatory response and a resulting coagulopathy and an increased microembolic load. 27 More commonly in today's practice, the cardiotomy suction and entire venous reservoir undergo hemoconcentration and ultrafiltration. This leads to decreased extravascular fluids with a higher hematocrit and removal of inflammatory mediators.…”
Section: Commentary 1 IImentioning
confidence: 99%
“…28 Similarly, cell salvage can reduce the concentration of inflammatory mediators by 90% to 95% and decrease the fat microembolic load by as much as 85%. 27,29 Unfortunately, cell salvage "washes out" the plasma and platelets. In a Jehovah's Witnesses patient, the decision to preserve plasma and platelets becomes very important and the use of the cardiotomy suction with appropriate hemoconcentration and ultrafiltration may be more beneficial.…”
Section: Commentary 1 IImentioning
confidence: 99%